Nondiseased Liver Stiffness Measured by Shear Wave Elastography: A Pilot Study. (1st January 2014) - Cha, Seung Woo; Jeong, Woo Kyoung; Kim, Yongsoo; Kim, Min Yeong; Kim, Jinoo; Kim, Soo Yeon; Ryu, Jeong Ah; Kim, Tae Yeob; Sohn, Joo Hyun; Kim, Young Hwan
Abstract : Objectives: The purpose of this study was to investigate the value of liver stiffness in patients without liver disease using shear wave elastography and to determine the liver stiffness threshold value for identifying patients with chronic liver diseases. Methods: A total of 150 patients who underwent liver sonography coupled with shear wave elastography were enrolled. On the basis of clinical and pathologic criteria, they were assigned to 1 of 2 groups: nondiseased liver (n = 97) and noncirrhotic chronic liver disease (n = 53). Liver stiffness was measured in the right liver, and the median value of 10 measurements was calculated. Both mean and median values in the nondiseased liver group were compared with those in the noncirrhotic chronic liver disease group. To validate this comparison, liver stiffness of the patients who underwent liver biopsy revealing either no fibrosis (fibrosis score F0; n = 5) or substantial fibrosis (F2; n = 14) was also investigated and compared. To determine the optimal threshold value for determining chronic liver disease, a receiver operating characteristic curve analysis was performed. Results: The mean liver stiffness value in the nondiseased liver group was 5.4 kPa. In the noncirrhotic chronic liver disease group, the mean value was 8.1 kPa. Differences between the nondiseased liver and both noncirrhotic chronic liver disease groups were statistically significant ( P < .001). The optimal liver stiffness threshold value for discriminating nondiseased liver from noncirrhotic chronic liver disease was 6.9 kPa. The sensitivity using this threshold was 94%. In the biopsy‐proven patients, the mean liver stiffness values were 6.0 kPa in the F0 group and 9.9 kPa in the F2 group. Conclusions: The range of liver stiffness in patients with nondiseased liver and the optimal threshold value for discriminating these patients from those with chronic liver disease were identified.